Synthesis and biological evaluation of combretastatin A-4 and three combretastatin-based hybrids (2012)
ABSTRACT: The syntheses of combretastatin A-4 from gallic acid and of three combretastatin-based hybrids are described. Starting from commercial gallic acid, thephosphonium salt (3,4,5-trimethoxybenzylphosphonium bromide) is synthesized and coupled, through a Wittig reaction, with several aldehydes, includingmethoxymethyl-protected isovanillin, the aldehyde γ-bicyclohomofarnesal having a labdane skeleton, 3-(3-pyridyl) propanal, and furfural. The biologicalproperties of the cis-coupled compounds as cytotoxic, antiviral and antifungal agents are also reported. In addition, pyrogallol, gallic and 3,4,5-trimethoxybenzoic acids have been studied biologically.